Developing norms and standards on maternal mortality in Africa: lessons from UN human rights bodies (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
ABSTRACT: The African Charter on Human and Peoples’ Rights and the Protocol to the African Charter Human and Peoples’ Rights on the Rights of Women in Africa (African Women’s Rights Protocol) contain useful provisions for addressing maternal mortality as a human rights violation. In addition, the African Union and its organs have recognised maternal mortality as a violation of the rights of women in Africa through initiatives such as the Campaign on Accelerated Reduction of Maternal Mortality in Africa; the African Commission on Human and Peoples’ Rights (African Commission) Resolution 135 on Maternal Mortality in Africa; as well as the African Commission’s General Comment on the Right to Life. Both the African Court on Human and Peoples’ Rights and the African Commission are now set to apply these frameworks in their jurisprudence and engagements with States. However, despite these developments, a significant number of African women die every year due to complications arising from pregnancy or childbirth. These deaths are avoidable if African governments have lived up to their obligations under international and regional human rights instruments. This article addresses pertinent experiences from the United Nations human rights system and analyses the key lessons learned from their approaches to addressing maternal mortality as a human rights issue, to strengthen the African system’s jurisprudence and legal frameworks. TITRE ET RÉSUMÉ EN FRANÇAIS: Le développement de normes et standards relatifs à la mortalité maternelle en Afrique: leçons apprises des organes des droits de l’homme des Nations Unies RÉSUMÉ: La Charte africaine des droits de l’homme et des peuples et le Protocole à la Charte africaine des droits de l’homme et des peuples relatif aux droits des femmes en Afrique (Protocole relatif aux droits des femmes en afrique) contiennent des dispositions utiles pour traiter la mortalité maternelle comme une violation des droits humains. En outre, l’Union africaine et ses organes ont reconnu la mortalité maternelle comme une violation des droits des femmes en Afrique à travers des initiatives telles que la Campagne pour la réduction accélérée de la mortalité maternelle en Afrique; la Résolution 135 de la Commission africaine des droits de l’homme et des peuples (Commission africaine) sur la mortalité maternelle en Afrique; ainsi que l’Observation générale de la Commission africaine sur le droit à la vie. La Cour africaine des droits de l’homme et des peuples et la Commission africaine peuvent désormais appliquer ces normes dans leur jurisprudence et dans leurs relations avec les Etats. Cependant, malgré ces développements, un nombre important de femmes africaines meurent chaque année en raison de complications liées à la grossesse ou à l’accouchement. Ces décès sont évitables si les gouvernements africains respectent leurs obligations en vertu des instruments internationaux et régionaux relatifs aux droits de l’homme. Le présent article traite des expériences pertinentes du système des droits de l’homme des Nations Unies et analyse les principaux enseignements tirés des approches par lesquelles ce système traite la mortalité maternelle en tant que question de droits de l’homme pour renforcer la jurisprudence et les cadres juridiques du système africain.
Keywords: African Commission on Human and Peoples’ Rights; African Court on Human and Peoples’ Rights; maternal mortality; maternal morbidity; resolutions on maternal mortality; United Nations human rights system